Perselisihan Penetapan Anggota Komisi Pemilihan Umum: Studi Penerapan Upaya Administratif - Muhammad Rinaldy Bima (CV. Social Politic Genius (SIGn), 2022)
This study aims to describe the position of the Selection Team at the State Administrative Court, as well as analyze dispute resolution procedures within the scope of the General Election Commission administration. This study uses a normative juridical method. The collected legal material is analyzed using qualitative data analysis methods with a statute approach to describe the problem and answer study purposes. The results show that the position of the Selection Team is a witness in the process of dispute resolution at the State Administrative Court. Furthermore, the detrimental parties may submit an objection and appeal effort. In this case, administrative dispute resolution has been regulated in General Election Commission Regulation No. 3 of 2021. On the other hand, Judges will only adjudicate cases and resolve disputes at the State Administrative Court after the plaintiff has undergone administrative efforts. Therefore, it is recommended for the Judge to reject lawsuits from the plaintiffs if the lawsuit positions the Selection Team as the defendant. In addition, it is also recommended that the plaintiff know and understand dispute resolution procedures on the determination of members of the General Election Commission at the State Administrative Court. In contrast, if the plaintiff has undergone administrative effort while the General Election Commission rejects the effort. So to get legal certainty, the plaintiff must submit a lawsuit by positioning the Commissioner of the General Election Commission as the defendant at the State Administrative Court.